Stock Verification of Electronic Publications: Rejoinder - Moorthy, A. Lakshmana (DESIDOC Journal of Library & Information Technology, 2003)
Stock Verification of Electronic Publications: A Rejoinder http://dx.doi.org/10.14429/dbit.20.6.3529